1975
DOI: 10.1210/jcem-41-4-722
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma TSH and Hypothyroidism in Children with Hypothalamic Hypopituitarism

Abstract: Basal TSH levels were found to be elevated in 6 patients with documented growth hormone deficiency and hypothyroidism. TRH (200 mug/m2 administered intravenously) led to an exaggerated TSH response. This is in contrast to the results in other GH-deficient children, with either a delayed rise of TSH (hypothalamic hypothyroidism due to TRH deficiency, n = 22), an absent TSH response (pituitary hypothyroidism due to TSH deficiency, n = 7), or a normal increase of TSH (isolated GH deficiency, n = 20). Elevated pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
17
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(24 citation statements)
references
References 0 publications
7
17
0
Order By: Relevance
“…Although unexpected, blood TSH levels were elevated in the TRH Ϫ͞Ϫ mice. There have been no patients with isolated TRH deficiency defined, but similar elevation has also been reported in some patients with central hypothyroidism (21). These patient's TSH activities were observed to be significantly reduced (22,23).…”
Section: Discussionsupporting
confidence: 55%
“…Although unexpected, blood TSH levels were elevated in the TRH Ϫ͞Ϫ mice. There have been no patients with isolated TRH deficiency defined, but similar elevation has also been reported in some patients with central hypothyroidism (21). These patient's TSH activities were observed to be significantly reduced (22,23).…”
Section: Discussionsupporting
confidence: 55%
“…It is reported that patients with hypothalamic lesions and IGHD often, but not invariably (Snyder et al 1974;Roitman et al 1980), show delayed and prolonged TSH responses to TRH (Hall et al 1972; Kaplan et al 1972;Faglia et al 1973;Illig et al 1975;Burger and Patel 1977;Okada et al 1978 ;Gamier et al 1983). In this study, all IGHD patients were of euthyroid state, but they showed delayed TSH responses to TRH as was seen also in 2ry GHD patients.…”
Section: Discussionsupporting
confidence: 60%
“…trartration (Hall et al 1972 ; Kaplan et al 1972 ;Faglia et al 1973 ; Illig et al 1975 ; Burger and Patel 1977 ;Okada et al 1978 ; Gamier et al 1983). Generally, there are two hormone pools, one is a readily releasable pool and the other is a newly synthesized pool, in endocrine cells (Hall et al 1972; Orci et al 1972;Bremner and Paulsen 1974).…”
mentioning
confidence: 99%
“…TSH deficiency was confirmed by a TRH test at the age of 1 yr after temporary discontinuation of T (22,23,30). Clinicians are accustomed to interpreting TRH tests by plotting the results at several time points after the administration of TRH, looking at the height of the peak TSH elevation and the shape of the curve.…”
Section: Trh Testsmentioning
confidence: 99%